Accuracy of sperm velocity assessment using the Sperm Quality Analyzer V - Hirano, Yuki (Reprod Med Biol, 2004)
Aim:  The correct diagnosis of the functional capacity of human sperm is limited. The Sperm Quality Analyzer (SQA) with the visualization system (SQA V, Medical Electronic System, Hatavorzo, Israel), an upgraded version of SQA, was recently developed to provide a rapid and low‐cost quantitative evaluation of sperm quality as well as sperm velocity assessment. The aim of the present study was to evaluate whether the SQA V's new parameters correlate with computer‐aided sperm analysis (CASA) estimates. Methods:  Semen quality analysis of 66 fresh samples was determined using SQA V and CASA. Results:  There were significant correlations of total sperm concentration (P < 0.001), sperm motility (P = 0.145), and percentage of progressive motile sperm (P = 0.001), between the SQA V variables and the CASA estimates. The sperm velocity assessed by SQA V was significantly correlated with some of the CASA estimates, including sperm motility (P = 0.001), the percentage of progressively motile sperm (P < 0.001), straight‐line velocity (P < 0.001), curvilinear velocity (P < 0.001) and average path velocity (P < 0.001). However, it did not correlate with amplitude of lateral head displacement, beat cross frequency, straightness, or linearity, assessed by CASA. Conclusion:  Assessment of sperm motility has been shown as one of the important factors to predict the functional capacity of human sperm. On the basis of the present study, SQA V is considered useful for screening sperm quality in the management of male infertility. (Reprod Med Biol 2003; 2: 151–157)